Digital transformation and financial development in emerging economies: regional variations and policy contingencies - Samson Edo (Digital Economy and Sustainable Development)
Abstract The role of digital transformation in financial development is investigated in this study, with the purpose of determining whether it is favourable as stipulated in the expectations of financial intermediation theory. In addition, the study seeks to determine variations in the role across emerging regions of the world. The regions under investigation are Mediterranean & North Africa, Latin America & Caribbean, and Sub-Saharan Africa. The investigation covers the period 2000–2023, and employs econometric techniques of generalized method of moments and panel vector error correction model, which possess the capacity to minimize bias and produce reliable results. The estimation results reveal that the role of digital transformation is significantly positive, which therefore suggest that the role satisfies the theoretical expectations. The role is strong in Sub-Saharan Africa, stronger in Latin America & Caribbean, and strongest in Middle East and North Africa. The positive role is complemented by monetary and fiscal policies, institutional quality, trade, and economic growth. The results are largely consistent and useful for policy making, hence the need to fine-tune relevant policies that can enhance the role of digital transformation and other control variables in driving financial development. Such policy measures may include relaxation of tariff on imported digital equipment and amendment of corporate tax policy to enable financial institutions invest more in digital technology. In addition appropriate measures need to be taken, to support the positive role of monetary and fiscal policies, institutional quality, trade, and economic growth in fostering financial development.